Engagement in meaningful activities post suicide loss: A scoping review - Monique Gill; Miranda Wu; Shania Pierre; Larine Joachim; Meera Premnazeer; Orianna Scali; Sakina J. Rizvi; Rebecca Renwick; Helene Polatajko; Jill I. Cameron (PLoS ONE, 2025)
Background Globally, more than 720,000 people die by suicide each year, leaving grieving individuals in their wake. Research indicates that individuals who lose a loved one to suicide face heightened risks for negative health outcomes. Recent studies show that taking part in meaningful activities can help protect health emphasizing the importance of exploring engagement in meaningful activities of everyday living among those bereaved. Currently, there has not been a review of the bereavement literature exploring the nature of, and extent to which, meaningful activities of everyday living are discussed. Objective To explore the nature of, and extent to which the peer-reviewed, suicide bereavement literature addresses engagement in meaningful activities of everyday living. Methods A scoping review following the Joanna Briggs Institute’s framework was completed to summarize and map the literature. Four electronic databases were searched for two concepts: suicide and bereavement. Studies were screened using specific inclusion and exclusion criteria. Two independent reviewers completed title and abstract, and full text screening for each article. All conflicts were resolved through discussion or by a third reviewer. Data were charted, summarized and results were reported using the PRISMA Extension for Scoping Reviews. Results 12372 studies were identified; 112 studies met inclusion criteria. Studies used qualitative (n = 90), quantitative (n = 10) and mixed (n = 12) methods. Findings indicate that the suicide bereavement literature discusses engagement in meaningful activities of everyday living using three main components: activities of everyday living, the engagement status of activities, and the meaning associated with activities. Discussion While references to meaningful activities of everyday living appear in the bereavement literature, they typically are discussed within the background rather than central research aims. There is a need to bring this discussion to the forefront and view engagement in meaningful activities of everyday living as an important aspect of suicide bereavement.